Analysis of behavioral interventions in alternative school settings. Issue 12 (4th September 2021) - Aspiranti, Kathleen; Mayworm, Ashley; Gadke, Daniel L.
Abstract: The purpose of this study was to conduct an analysis of the effects of behavioral interventions used in alternative school settings on student outcomes, including group design (GD) and single‐case design (SCD) studies. Behavioral interventions were broadly defined as interventions targeting behavior or thoughts and feelings, but not academics. An alternative school setting is defined as, "A public elementary/secondary school that (1) addresses needs of students that typically cannot be met in a regular school, (2) provides nontraditional education, (3) serves as an adjunct to a regular school, or (4) falls outside the categories of regular, special education, or vocational education" (National Center for Education Statistics,  2017). Studies meeting What Works Clearinghouse design standards for GD and SCD were included. A total of 21 eligible studies (13 GD; 8 SCD) were included across peer‐reviewed journal articles and dissertations. The GD studies included a total of 1202 participants and SCD included 105 participants. Hedges' g effect sizes measures were calculated separately for GD and SCD studies. Results indicate interventions in alternative settings have at least moderate effects on behavioral and emotional outcomes; these effects were higher for SCD studies. There were no significant moderators for GD studies, but outcomes were moderated by grade and race for SCD studies. The need for future studies with increased methodological rigor is discussed.